Extracellular vesicles as circulating cancer biomarkers: opportunities and challenges. Issue 1 (31st May 2018) - Lane, R. E.; Korbie, D.; Hill, M. M.; Trau, M.
Abstract: Extracellular vesicles (EVs) are small, lipid‐bound particles containing nucleic acid and protein cargo which are excreted from cells under a variety of normal and pathological conditions. EVs have garnered substantial research interest in recent years, due to their potential utility as circulating biomarkers for a variety of diseases, including numerous types of cancer. The following review will discuss the current understanding of the form and function of EVs, their specific role in cancer pathogenesis and their potential for non‐invasive disease diagnosis and/or monitoring. This review will also highlight several key issues for this field, including the importance of implementing robust and reproducible sample handling protocols, and the challenge of extracting an EV‐specific biomarker signal from a complex biological background.